2020
DOI: 10.1186/s13014-020-01693-2
|View full text |Cite
|
Sign up to set email alerts
|

Report on planning comparison of VMAT, IMRT and helical tomotherapy for the ESCALOX-trial pre-study

Abstract: Background The ESCALOX trial was designed as a multicenter, randomized prospective dose escalation study for head and neck cancer. Therefore, feasibility of treatment planning via different treatment planning systems (TPS) and radiotherapy (RT) techniques is essential. We hypothesized the comparability of dose distributions for simultaneous integrated boost (SIB) volumes respecting the constraints by different TPS and RT techniques. Methods CT data sets of the first six patients (all male, mean age: 61.3 yea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Although a number of studies enrolled a limited number of patients, they all succeeded to show the differences regarding PTV coverage. 7 , 11 , 12 While Clemente et al and Stieler et al achieved lower values for CI for VMAT plans, thus demonstrating the superiority of VMAT over IMRT, Pigorsch et al obtained equal coverage factors (CVF) for IMRT and VMAT for PTV77 and PTV56. 7 , 11 , 12 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although a number of studies enrolled a limited number of patients, they all succeeded to show the differences regarding PTV coverage. 7 , 11 , 12 While Clemente et al and Stieler et al achieved lower values for CI for VMAT plans, thus demonstrating the superiority of VMAT over IMRT, Pigorsch et al obtained equal coverage factors (CVF) for IMRT and VMAT for PTV77 and PTV56. 7 , 11 , 12 …”
Section: Resultsmentioning
confidence: 99%
“… 7 , 11 , 12 While Clemente et al and Stieler et al achieved lower values for CI for VMAT plans, thus demonstrating the superiority of VMAT over IMRT, Pigorsch et al obtained equal coverage factors (CVF) for IMRT and VMAT for PTV77 and PTV56. 7 , 11 , 12 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since IMRT is characterized by typically arranging less than 9 fixed-field beam angles, VMAT instead has numerous beam directions from the arc trajectory. Thanks to there being no beam modulation by the MLCs, VMAT achieves less high-dose areas, more homogeneous dose distribution, and better spare to the salivary glands while treatment beams are sequenced one after another in IMRT treatment plan [ 22 ]. Some researchers found that the isodose distribution in IMRT approaches to VMAT as increasing numbers of beams are utilized [ 23 ].…”
Section: Discussionmentioning
confidence: 99%